2016
DOI: 10.1080/10503307.2016.1169331
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence resolution in emotion-focused therapy: The successful case of Sarah

Abstract: Although it has been suggested that integrating opposing parts of the self is a necessary process for psychotherapeutic success, a less integrative process of ambivalence resolution may also be an important resource along the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 27 publications
5
31
1
4
Order By: Relevance
“…Besides starting treatment with different proportions of negotiation, recovered and unchanged cases also differ in terms of the proportion of negotiation across sessions: recovered cases increase its proportion while unchanged cases seem to maintain low levels of negotiation throughout the whole treatment. This result corroborates Braga et al () suggestion that successful ambivalence resolution calls for an increasing negotiation between the opposing positions of the self that are involved in it. This is also in line with EFT's (Greenberg & Watson, ) assumption that the dialogue between positions is essential to emotional processing that, in turn, is crucial for successful therapy, and with the assimilation model's (Stiles, ; Stiles et al, ) proposal of an increasing assimilation of problematic experiences in successful psychotherapeutic processes.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Besides starting treatment with different proportions of negotiation, recovered and unchanged cases also differ in terms of the proportion of negotiation across sessions: recovered cases increase its proportion while unchanged cases seem to maintain low levels of negotiation throughout the whole treatment. This result corroborates Braga et al () suggestion that successful ambivalence resolution calls for an increasing negotiation between the opposing positions of the self that are involved in it. This is also in line with EFT's (Greenberg & Watson, ) assumption that the dialogue between positions is essential to emotional processing that, in turn, is crucial for successful therapy, and with the assimilation model's (Stiles, ; Stiles et al, ) proposal of an increasing assimilation of problematic experiences in successful psychotherapeutic processes.…”
Section: Discussionsupporting
confidence: 90%
“…In unchanged cases, the proportion of dominance is high and stable across sessions, whereas negotiation seems to be virtually absent throughout the entire treatment. Braga et al () had already identified a high frequency of dominance across sessions in a recovered case and this study corroborates this finding. We believe these results encourage a further reflection on the status of the dominance process of ambivalence resolution.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations